Esterase enzymes involved in pyrethroid and organophosphate resistance in a Brazilian population of Riphicephallus (Boophilus) microplus (Acari, Ixodidae) - Baffi, Milla Alves [UNESP]; Lino de Souza, Guilhermle Rocha; de Sousa, Cristina Soares; Ceron, Carlos Roberto [UNESP]; Bonetti, Ana Maria (Elsevier B.V., 2008)
Esterases are a group of enzymes that are reportedly associated with acaricide resistance in Riphicephallus (Boophilus) microplus. A comparative analysis was made of the esterase patterns in malathion and deltamethrin-sensitive, tolerant and resistant tick groups, using non-denaturing polyacrylamide gel electrophoresis. Electrophoretical profiles revealed four bands of esterase activity against alpha-naphthyl acetate; which were dubbed EST-1 to EST-4. The EST-3 and EST-4 were detected in all strains and were classified as carboxylesterases (CaEs). The EST-2, classified as an acetylcholinesterase (AChE), was detected in all groups, but its staining intensity increased from susceptible to resistant groups, indicating an altered production according to the degree of resistance. EST-1, which was also classified as an AChE, was detected exclusively in tolerant and resistant groups to both acaricides, but displayed greater activity in the malathion-resistant group. These data suggest that these AChEs may represent an important detoxification strategy developed to overcome the effects of acaricides. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acaricide resistance; Acetylcholinesterase; Carboxylesterase; cattle tick